Thrombinography shows acquired resistance to activated protein C in patients with lupus anticoagulants - Regnault, Véronique; Béguin, Suzette; Wahl, Denis; de Maistre, Emmanuel; Coenraad Hemker, H.; Lecompte, Thomas (Thrombosis and Haemostasis, 2003)
In patients with lupus anticoagulants (LA), acquired resistance to activated protein C (APC) is difficult to demonstrate with clot-based assays due to the presence of the anticoagulant. Via the conversion of a fluorogenic substrate (thrombinography), we monitored the complete process of thrombin formation and decay and its delimitation by the protein C system in eight consecutive LA-patients without anticoagulant therapy and non-carriers of the V Leiden polymorphism. Thrombin generation was triggered in platelet-poor and platelet-rich plasma by recalcification in the presence of a low concentration of tissue factor.In 7 out of 8 patients we observed a long lag-time before the thrombin burst (LA effect) together with a marked inability of APC to diminish the thrombin activity. The lag-phase was however prolonged to some degree by APC. The effects were more outspoken in the presence of phospholipids from patients' platelets than with added phospholipids.Thrombinography thus demonstrates APC resistance in LA-patients despite the occurrence of long lag-times (clotting times). The amount of thrombin activity generated in the presence of APC could be a better indicator of the thrombotic risk than the moment at which the thrombin burst starts.
Keywords: Lupus anticoagulant; acquired APC resistance; thrombin activity; platelets